The development of STEM-based DIGASS application to improve college student assessment skills - Ermawati, Diana; Hilyana, F. Shoufika; Riswari, Lovika Ardana (Indonesian Research Journal in Education |IRJE|, 2024)
Assessment application is essential because college students, as prospective teachers, must be able to assess students to find out the right treatment in the process of achieving learning goals. This research aimed to develop the STEM-based DIGASS application to improve college student assessment skills in the era of Society 5.0. This research used Research and Development (R&D) procedures with stages 1) potential and problems, 2) data collection, 3) product design, and 4) design validation. The subjects of this research were college students of the Faculty of Teacher Training and Education, Universitas Muria Kudus. The research instrument used digital assessment needs analysis, prototype development, and digital assessment prototype validation results data. The results of this research found that the STEM-based DIGASS application is feasible to use to determine college student assessment skills with average results in terms of Usability (4.07), Functionality (4.50), and Visual Communication (4.25).